Answer:
y=-3x
Step-by-step explanation:
Slope intercept form is written as y=mx+b, where:
m= slope
b= y-intercept
We know the slope and y intercept already, so simply plug them in:
y=-3x+0
We can remove the +0 because it is redundant, therefore the final answer is:
y=-3x
why?
ωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωωω
Answer:
b
Step-by-step explanation:
sorry if i am wrong
Answer:
I think the right answer is 3 I. E deviation abi